2014
DOI: 10.1111/jan.12447
|View full text |Cite
|
Sign up to set email alerts
|

Adherence in patients in the first year after kidney transplantation and its impact on graft loss and mortality: a cross‐sectional and prospective study

Abstract: Patients with poor adherence to the immunosuppressive medication in the first year after kidney transplantation showed increased likelihood of graft loss and death over 12 years compared with the adherent patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 49 publications
5
62
3
Order By: Relevance
“…[17] The results showed that most patients had good adherence to taking medication and various studies have confirmed these findings. [4131518] Patients adherence in this study was higher than that reported in the study by Shabany Hamedan et al .,[19] which might be due to increased awareness of the patients regarding the importance of taking certain medications. Patients' adherence was affected by various factors.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…[17] The results showed that most patients had good adherence to taking medication and various studies have confirmed these findings. [4131518] Patients adherence in this study was higher than that reported in the study by Shabany Hamedan et al .,[19] which might be due to increased awareness of the patients regarding the importance of taking certain medications. Patients' adherence was affected by various factors.…”
Section: Discussioncontrasting
confidence: 63%
“…Patients who used medication observed better performance of the transplanted organ, and despite experiencing side effects, they still used the medications. [18] Therefore, educating the patients about the side effects as well as the importance of using drugs, despite the complications that are not life-threatening, is necessary. The results of the present study indicated that the patients who were greatly supported by their family compared to other patients had good adherence to using medications, which is in agreement with other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eventhough there is the risk of social desirability with patient-reported non-adherence assessment (as it is with all self-report variables), patient-reported non-adherence has been shown to be associated with rejection [1, 1012] and graft loss [1, 2, 6, 11, 13]. However, some studies failed to prove this association [6, 14].…”
Section: Introductionmentioning
confidence: 99%
“…There is an obvious relationship between the discontinuity in the use of immunosuppressive drugs and the incidence of transplant failures in the medium and long term[4]. Non-adherence to the transplant medication regimen can lead to graft rejection, post-transplant mortality, increase in healthcare costs, and decrease in quality of life[5,6]. One meta-analysis found non-adherence to medication across all organ transplants to be 22.6%[7].…”
Section: Introductionmentioning
confidence: 99%